Experimental-simulation analysis on mechanical degradation and energy evolution characteristics of sandstone under water-rock coupling effects - Yu Yongjiang; Guo Wenjing; Liu Jiaming; Wu Zhiqiang; Dong Xu (Scientific Reports)
Abstract With increasing coal mining depths, water-rock interactions exacerbate the mechanical degradation of coal-rock masses and geological disaster risks. Investigating the mechanical properties and energy evolution mechanisms of water-bearing sandstone is crucial for ensuring safe mining operations. To address the existing research gap in analyzing energy evolution mechanisms of water-saturated rock masses from a macroscopic perspective and the lack of exploration into energy mechanisms at critical failure points at the mesoscale, this study employs the particle discrete element software PFC3D to establish numerical models of sandstone with varying water contents. Combined with uniaxial compression tests and energy calculation principles, the mechanical degradation laws and energy evolution characteristics of sandstone under water-rock interactions are systematically investigated. The results indicate that the mechanical properties of sandstone exhibit significant degradation with prolonged immersion time, where compressive strength and elastic modulus gradually decrease with increasing water content. Energy evolution during sandstone deformation and failure can be divided into three stages: elastic energy storage, crack propagation energy dissipation, and sudden energy release at failure. Water immersion significantly reduces energy absorption efficiency during the elastic storage stage and increases energy dissipation rates during crack propagation. Mesoscale crack development analysis reveals that water accelerates the extension of initial fractures and the initiation of new cracks, while higher water content promotes a transition from localized to diffuse crack distribution. Additionally, the energy thresholds at critical failure points and failure modes of samples with different water contents show significant correlations, revealing the dynamic regulatory mechanism of water-induced weakening effects on energy accumulation and release in sandstone. These findings provide theoretical support for safe mining and dynamic disaster prevention in deep water-rich coal seams.